Climate Change, Environmental Components And Media, Climate Village Program (PROKLIM) And Covid-19 - Azizah, R.; Sulistyorini, Lilis; Husnina, Zida; Salsabila, Zaneta Aaqilah; Naura, Zafira Nuha (VISIKES, 2025)
Background: In early January 2020, the COVID-19 pandemic affected all countries globally. The resulting reduction in vehicular mobility during the pandemic period temporarily eased pressure on the environment by lowering greenhouse gas emissions. Consequently, attention to environmental components-particularly the physical and biological aspects of water and air media-has become increasingly important.Methods: This study employed a quantitative approach, gathering data through surveys distributed to participants of a webinar attended by 500 individuals. The survey was disseminated via a Google Form shared through the Zoom chat feature. Data were analyzed using SMART PLS Version 4 to determine the relationship between environmental components and environmental media.Results: Analysis of responses from 500 participants indicated that the majority prioritized water and air environmental media. This was supported by high loading factor values for the water environment (0.782) and air environment (0.760). The Structural Equation Modeling (SEM) analysis revealed that environmental components significantly influence environmental media, with a T-statistic value of 64.119 and a p-value of 0.000 (T > 1.96, p < 0.05).Conclusion: Environmental components have a significant effect on environmental media, underscoring the importance of environmental management. The Climate Village Program (Program Kampung Iklim) emerges as a potential community-based initiative to mitigate climate-related diseases, including airborne transmission of COVID-19.